Parents’ Marital Status, Conflict, and Role Modeling: Links With Adult Romantic Relationship Quality - Rhoades, Galena K. (2012)
This study investigated three parental marital statuses and relationship quality among unmarried, but dating adults ages 18 to 35 (N = 1153). Those whose parents never married one another tended to report the lowest relationship quality (in terms of relationship adjustment, negative communication, commitment, and physical aggression) compared to those with divorced or married biological parents. In addition, those with divorced parents reported lower relationship adjustment and more negative communication than those with married parents. Parental conflict and the degree to which participants rated their parents’ relationship as a healthy model for their own relationships partially explained the associations between parental marital status and relationship outcomes. We suggest that this particular family type (i.e., having parents who never marry one another) needs greater attention in this field in terms of research and intervention.